The cost of funds to commercial banks : an econometric analysis - Magen, S. D. (New York : Dunellen, 1971)
The book is an attend to examine how the cost of capital behaves with changes in the capital structure. It is a study aimed at investigating the problems in the commercial banking industry..
Bibliography: p. 159-165.
usc 16/05/2017
Loans
Keywords: Banks and banking